OSCILLATORY CONVECTIVE PROCESSES IN NANO- AND MICROFLUIDIC SYSTEMS: ANALYSIS AND CONTROL - Maryshev, B.S.; Alabuzhev, A.A.; Babushkin, I.A.; Glukhov, A.F.; Demin, V.A.; Myznikova, B.I.; Popov, E.A.; Fayzrakhmanova, I.S.; Cherepanov, I.N.; Shklyaev, S.V. (Perm Federal Research Centre Journal, 2016)
This publication contains the main results of the work on the RFBR project 13-01-96010 r_ural_a«Oscillatory convection processes in nano- and microfluidic systems: analysis and control». The aim of this project is an experimental and theoretical study of complex convective phenomena innonisothermal nanofluids and thin films. A common attribute of the systems under consideration is the presence of an oscillatory mode of instability of their ground state or the first critical mode. The dynamics of the systems under consideration in periodic external conditions is interesting because of (1) complex and not fully explained kinetics; (2) a rich bifurcation picture and (3) the technological necessity in the management of stability and non-linear modes of macroscopic flows of nanofluids and microfluidic flows.